Prevalence of vitamin D deficiency and its association with metabolic derangements among children with obesity - S. G. S. Adikaram; D. B. D. L. Samaranayake; N. Atapattu; K. M. D. L. D. Kendaragama; J. T. N. Senevirathne; V. Pujitha Wickramasinghe (BMC, 2019)
Abstract Background It is known that obesity is associated with vitamin D deficiency and observational studies have shown vitamin D deficiency to be linked with the development of type 2 diabetes. There are no comprehensive data regarding vitamin D deficiency in children with obesity in Sri Lanka and the objective of the study was to assess the prevalence of Vitamin D deficiency and its association with metabolic derangements among children with obesity. Methodology Two hundred and two children between 5 and 15 years of age attending the obesity clinic Lady Ridgeway Hospital (LRH) were recruited excluding those having possible secondary causes for obesity. Blood was drawn after 12-h overnight fast for fasting blood glucose(FBG), lipid profile, serum insulin, alanine aminotransferase (ALT),aspartate aminotransferase(AST), Vitamin D, parathyroid hormone(PTH),high sensitivity C reactive protein(hs-CRP). Oral glucose tolerance test (OGTT) was done with 2 h random blood glucose. Anthropometry, blood pressure were measured, and body fat mass was assessed using bio-impedance. Results Vitamin D deficiency (< 20 ng/ml) was seen in 152(75.2%) children and 43(21.3%) had insufficient (20-30 ng/ml) levels. Skin fold thickness, fasting and post-glucose insulin, HOMA-IR, PTH, LDL, Serum cholesterol and hs-CRP showed statistically significant negative correlations with Vitamin D levels. Conclusions Vitamin D deficiency was significantly high in Sri Lankan children with obesity and showed significant negative correlations with indicators of insulin resistance and adiposity.